2018
DOI: 10.1093/cid/ciy090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Timing of Influenza Vaccination in Pregnancy on Transplacental Antibody Transfer, Influenza Incidence, and Birth Outcomes: A Randomized Trial in Rural Nepal

Abstract: This placebo-controlled randomized trial in rural Nepal found that maternal influenza vaccination in either the second or third trimester of pregnancy provided similar birth outcomes and protection from influenza in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…Blanchard-Rohner et al showed that receipt of influenza vaccine at least 2 weeks before delivery increased umbilical cord HIA titers and seroprotection rates in newborns (154). Finally, Katz et al found no significant differences in influenza HIA titers in cord sera of women vaccinated early (17-25 weeks gestation) or later (26-34 weeks gestation) in randomized trials during pregnancy (155).…”
Section: Timingmentioning
confidence: 99%
“…Blanchard-Rohner et al showed that receipt of influenza vaccine at least 2 weeks before delivery increased umbilical cord HIA titers and seroprotection rates in newborns (154). Finally, Katz et al found no significant differences in influenza HIA titers in cord sera of women vaccinated early (17-25 weeks gestation) or later (26-34 weeks gestation) in randomized trials during pregnancy (155).…”
Section: Timingmentioning
confidence: 99%
“…Importantly, in Nepal, women were randomized to second or third trimester vaccination to evaluate whether timing of vaccination during pregnancy would affect efficacy. No difference in efficacy was observed by trimester of vaccination (45).…”
Section: Influenzamentioning
confidence: 77%
“…In these settings, influenza vaccination may be considered as a year-round vaccination strategy and has been shown to be efficacious in a randomized clinical trial of maternal influenza vaccination in Nepal [14]. In this study, women were additionally randomized to second or third trimester vaccination to evaluate the effect on infant influenza vaccine efficacy [115]. The results from this study showed that there was no significant difference in influenza vaccine efficacy by second or third trimester vaccination, and there was a nonsignificant trend towards improved birth weight with earlier vaccination.…”
Section: Timing Of Maternal Immunizationmentioning
confidence: 99%